2020
DOI: 10.1016/j.metabol.2019.154041
|View full text |Cite
|
Sign up to set email alerts
|

Serum endotoxin, gut permeability and skeletal muscle metabolic adaptations following a short term high fat diet in humans

Abstract: Background: Our previous work demonstrated that a short-term high fat diet (HFD) increased fasting serum endotoxin, altered postprandial excursions of serum endotoxin, and led to metabolic and transcriptional responses in skeletal muscle in young, healthy male humans. Purpose: The purpose of the present study was to determine if a short-term high fat diet: 1) increases intestinal permeability and, in turn, fasting endotoxin concentrations and 2) decreases postprandial skeletal muscle fat oxidation. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The third hypothesis, that the clinical SINS score could be improved through improved husbandry (e.g., better supply of water and fibre), was also confirmed. This hypothesis is based on experience from working farms and published results on intestinal health: Microbiota dysbiosis and intestinal barrier impairment are associated with the development of a number of chronic inflammatory disorders and systemic diseases in humans (for a review, see [ 1 , 68 ]) and the pathogenic involvement of endotoxins has been reviewed [ 4 , 5 , 9 , 17 ]. Thanks to continuous monitoring by the herd health service of Baden-Wurttemberg, specific infectious intestinal diseases can be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The third hypothesis, that the clinical SINS score could be improved through improved husbandry (e.g., better supply of water and fibre), was also confirmed. This hypothesis is based on experience from working farms and published results on intestinal health: Microbiota dysbiosis and intestinal barrier impairment are associated with the development of a number of chronic inflammatory disorders and systemic diseases in humans (for a review, see [ 1 , 68 ]) and the pathogenic involvement of endotoxins has been reviewed [ 4 , 5 , 9 , 17 ]. Thanks to continuous monitoring by the herd health service of Baden-Wurttemberg, specific infectious intestinal diseases can be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was approved by the Virginia Polytechnic Institute and State University Institutional Review Board (#06-367) and both written and verbal informed consent were obtained from each participant. The present study was a secondary analysis that relied on stored blood samples collected from a study in which the experimental design and procedures have been described previously (Baugh et al, 2020;Bowser et al, 2020). Therefore, our sample size was limited to males in our previous study focused on skeletal muscle metabolism because in our experience females have declined to undergo the biopsy procedures (Baugh et al, 2020;Bowser et al, 2020).…”
Section: Participantsmentioning
confidence: 99%
“…The purpose of this investigation was to test the hypothesis that fasting and postprandial TMAO concentrations are reduced in endurance-trained males compared with sedentary males before and following a HFD. Our sample was limited to that included in the parent study which focused on skeletal muscle metabolism (Baugh et al, 2020;Bowser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Seventeen metabolically healthy, SED (self-report of Ͻ2 h of physical activity per week for at least the last 3 mo and no planned, intentional exercise) and seven ET (self-report of running for Ն5 h per week and participating in Ն2 running races of Ն10 km in the last year) males without obesity and aged 18 -40 yr completed the study. Thirteen SED were participants in a prior study involving the same outcomes (10). Participants self-reported weight stability (Ϯ2.5 kg) for the prior 6 mo and had a body mass index between 18 and 30 kg/m 2 .…”
Section: Participantsmentioning
confidence: 99%
“…The relationship between a high-fat diet (HFD) and habitual physical activity behavior and their combined effect on skeletal muscle substrate metabolism is not well understood. Recently, we showed that metabolically healthy, SED individuals have an altered postprandial fat (10) and glucose oxidation (3,10) response to an HFD; however, whether substrate metabolism is modified by a HFD in endurance-trained (ET) individuals is not known. Therefore, the objective of the present study was to determine the influence of an HFD on fasting and postprandial skeletal muscle substrate metabolism in ET compared with SED males.…”
Section: Introductionmentioning
confidence: 99%